Huntington Beach 4th of July Parade with Watkins Family and Model T Ford - Watkins, Howard::::::::: (1988)
?, Howard Watkins wearing Cherokee Indian headdress standing on running board, Albert Watkins, Jerry Kamp, Adam Watkins, Frances Kamp, and Rose O'Reilly